THE INTERCULTURAL SENSITIVITY IN PAULO FREIRE - Norman Estupiñán Quiñones, Núbia Cecilia Agudelo Cely, (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
Sense and meaning of relationship with others become a thought articulator axle and Paulo Freire’s educational practices as well. From this perspective, the conceptualizations and the cultural value assigned to the cultural sensibility stem from them. Such a cultural sensitivity is understood as projection and positive emotional answers as to others, deep curiosity promotion, critical thought, respect and world appraisal, and others’ interests and knowledge. The ideas exposed become a primordial objective of this presentation. For that, fundamental Freire’s work was revised, such as Pedagogía del Oprimido, Pedagogía dela Esperanza, y Pedagogía de la autonomía, as well as, of course, revision of other autors and arguments, which served as support for the previous publications.